Clinical attachment loss may serve as a more precise, suitable, and pragmatic grading instrument for periodontitis: A clinical and radiographic validation study - Meer, Rayan M. (2024)
ObjectiveThe present study was aimed at assessing the sensitivity and accuracy of using clinical attachment loss (CAL) as a substitute tool for grading periodontitis, instead of the interdental bone loss (BL) percentage derived from two-dimensional radiographs. MethodsOne hundred patients diagnosed with periodontitis were included in the study. Periodontitis was graded according to the American Academy of Periodontology (AAP) 2017 classification. In the first part of this validation study, the BL percentage was calculated from periapical and panoramic radiographs and compared with cone beam computed tomography (CBCT). CAL was measured and divided by root length, and was subsequently used as a substitute for BL in periodontitis grading. The agreement and percentage agreement among CAL grading, periapical radiographs, panoramic radiographs, and CBCT grading were assessed. ResultsBoth the periapical and panoramic radiographs showed a lack of agreement with CBCT grading, whereas CAL grading showed a moderately higher level of agreement (fair agreement) with CBCT grading. ConclusionThe accuracy of two-dimensional imaging-based BL assessment for grading periodontitis appears questionable. In contrast, the ratio of CAL to root length might be a more accurate, user-friendly, and practical tool for grading periodontitis. However, further well-designed studies remain necessary to confirm the present results.